Pinching of gel-filled honeycomb. (5th December 2022) - Shalchy, Faezeh; Carlsson, Jenny; Deshpande, Vikram; Fleck, Norman
Abstract: The effect of gel-filling of a hexagonal honeycomb upon its transverse compressive response is investigated experimentally and numerically. The specimens comprise square tubes with sealed ends and are made from aluminium alloy honeycomb. The specimens are loaded transversely between frictionless flat platens at their mid-length. It is shown experimentally and by finite element simulation that gel-filling of the hexagonal honeycomb in the closed-ended tubes changes the deformation mode in the pinched zone from that of the empty honeycomb. The pinch load increases with increasing displacement, with no evidence of crush band formation. The highly stable response is due to the presence of the incompressible gel-core, and due to the build-up of membrane tension, in the axial direction, within the walls of the honeycomb. As pinching proceeds, axial flow of the gel occurs from the shrinking, pinched zone to the outer, free-standing, dilating portions of the tube. Additional finite element simulations quantify the sensitivity of pinch strength to the inclination of the cell walls of the honeycomb, and to the presence of geometric imperfections within the honeycomb.